THERAPEUTIC PROPERTIES OF SOME SPECIFIC HONEY TYPES - Jovanov, Pavle; Sakač, Marijana; Marić, Aleksandar; Plavšić, Dragana; Jakimov, Dimitar; Đermanović, Branislava (Food and Feed Research, 2024)
This paper examines the physicochemical characteristics, as well as the antioxidant, antibacterial, and antiproliferative effects, of several honey types that are commercially available but not typical of Serbia. The analysis included moisture, pH, electrical conductivity, free acidity, and hydroxymethylfurfural (HMF). All tested honey samples met EU regulatory standards. The antioxidant activity was assessed by measuring total phenolic content (TPC) and scavenging activity on diphenylpicrylhydrazyl radicals (DPPH•). Forest honey exhibited the highest TPC level (30.6 ± 1.63 mg GAE/100 g), while buckwheat honey had the lowest (14.4 ± 0.75 mg GAE/100 g). This was consistent with the scavenging activity on DPPH•, which was the highest in manuka honey and lowest in buckwheat honey. Antibacterial activity was evaluated using agar diffusion tests and minimal inhibitory concentration (MIC) measurements. Manuka honey demonstrated the strongest antibacterial effects against Staphylococcus aureus and S. epidermidis, with a MIC of 6.25% for both strains. Buckwheat honey also showed notable antibacterial activity against these strains. In terms of antiproliferative activity, manuka honey was the most effective among the tested honey types, with IC50 values of 21.9 ± 2.05 mg/mL for cervix cancer cells (HeLa) and 32.5 ± 3.69 mg/mL for MRC-5 cells derived from healthy lung tissue.